W.E.B. Du Bois : the lost and the found - Basevich, Elvira (Cambridge, UK ; Medford, MA : Polity, 2021)
'A totally fresh account of Du Bois and why his life and legacy remain as vital as ever.'--
Part I - Inclusion -- Du Bois and the Black Lives Matter Movement: Thinking with Du Bois about Anti-Racist Struggle Today -- Student Days, 1885-95: Between Nashville, Cambridge, and Berlin -- The Emergence of a Black Public Intellectual: Du Bois's Philosophy of Social Science and Race (1895-1910) -- Part II - Self-Assertion -- Courting Controversy: Du Bois on Political Rule and Educated'Elites' -- A Broken Promise: On Hegel, Second Slavery and the Ideal of Civic Enfranchisement (1910-1934) -- Du Bois on Sex, Gender, and Public Childcare -- Part III - Despair -- Self-Segregation and Self-Respect (1934-1951): A Liberalism Undone? -- Conclusion The Passage into Exile: The Return Home Away from Home (1951-1963).
Includes bibliographical references and index.
Keywords: Du Bois, W. E. B. -- 1868-1963.; Du Bois, W. E. B. -- 1868-1963 -- Criticism and interpretation; African Americans -- Biography; African American authors -- Biography; African American civil rights workers -- Biography; Civil rights workers -- United States -- Biography; African Americans -- Civil rights -- History